Sinapic acid ameliorates cisplatin‐induced disruptions in testicular steroidogenesis and spermatogenesis by modulating androgen receptor, proliferating cell nuclear antigen and apoptosis in male rats. (8th January 2022) - Demir, Murat; Altındağ, Fikret
Abstract: The chemotherapeutic cisplatin, which is widely used in many cancer types, causes testicular toxicity. Sinapic acid has many therapeutic effects such as antioxidant, anti‐inflammatory and antihyperglycaemic. This study aimed to investigate the improving effects of sinapic acid in cisplatin‐induced testicular toxicity. Twenty‐eight rats were distributed into 4 groups. Control group: saline was applied intraperitoneal. Cisplatin group: A single dose of 7 mg/kg of cisplatin was injected into rats. Cisplatin +Sinapic acid group: 3 days after a single dose of 7 mg/kg cisplatin was injected, 25 mg/kg of sinapic acid was given for 7 days. Sinapic acid group: rats were received 25 mg/kg/day of sinapic acid. Numerical density of spermatogonium, Leydig and volume density of germinal epithelial were calculated. Caspase‐3, Bcl‐2, AR and PCNA expressions in testis were evaluated and testosterone and LH levels were measured. Cisplatin application decreased the numerical density of spermatogonium and Leydig, volume density of germinal, epididymal sperm count, testosterone, LH and the expressions of Bcl‐2, AR and PCNA in testis. However, sinapic acid treatment significantly restored the parameters of our study. The results of the present study revealed that cisplatin can cause male reproductive toxicity and sinapic acid can have improving effects against cisplatin‐induced male reproductive toxicity.